Implementasi Efek Caustic Pada Objek Transparan Dengan Menggunakan Ray Tracing - Yoewono, Edward Primanata; -, Liliana; Intan, Rolly (Jurnal Infra, 2015)
Rendering is the process by the end of the whole process of modeling or computer animation to change the form of three-dimensional objects into two dimensions. One popular method of rendering known today is ray tracing. Ray tracing is a technique for generating an image by tracing the path of light through pixels in the image.Ray tracing method is able to produce realistic images because it is calculating lighting effects such as ambient, diffuse and specular. Reflection and refraction of light is also calculated in ray tracing. In addition, ray tracing method is divided into two kinds, known as the tracing rays from the eye (backward ray tracing) and tracing rays from the light source (forward ray tracing).Caustic effect produced by emitting light in a transparent object. Refracted light will gather in an area so that the area will appear brighter than the surrounding areas. In previous studies, the effect of caustic applied to the primitive object, where the light checks done once per object. In this study, the object used is mesh. Checking the light will be performed on each triangle in the mesh.Results showed the greater refractive index, the more caustic effect gathered in certain areas of the body bare round, but spread on a flat and taper grounded object. The increase in the complexity of the mesh will increase linearly time. Comparison with other software shows the difference in the form of caustic effects and rendering time.